Influence of Weight-Age Normalization on Glomerular Filtration Rate Values of Renal Patients: A STROBE-Compliant Article. Issue 3 (January 2016) - Li, Li; Hongwei, Si; Ying, Qiao; Jianzhong, Liu; Zhifang, Wu; Ling, Gao; Sijin, Li
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: To explore whether weight-age (W-A) could be applied in clinical practice, this study was designed to verify the normalization ability of W-A by the data from another medical center, and to access the influence of the normalization on glomerular filtration rate (GFR) values in renal patients. Both plasma clearance (pGFR) and camera-based (gGFR), which were separately scaled to W-A and body surface area (BSA), were measured for patients with diffuse renal diseases. The patients (n = 298) were stratified according to the Chinese body mass index (BMI) criteria and were staged according to the Kidney Disease Outcome Quality Initiatives guideline based on gGFR and pGFR separately. The indices of intraclass correlation coefficient (ICC), concordance correlation coefficient (CCC), and ratio of residual standard deviation to pooled standard deviation (RSD/PSD) suggested that, for all patients and each BMI stratum, W-A was obviously better than BSA in scaling GFR. Both under pGFR or gGFR renal stages, only small amount of the patients encountered stage migrations from BSA to W-A scaled stages. The differences between any 2 of the unscaled, BSA scaled, and W-A scaled gGFR (or pGFR) were not obviously changed. Additionally, in some strata, W-A normalization is better than BSA normalization in decreasing the median bias between pGFR and gGFR. W-A is better than BSA in scaling GFR without obvious modifying GFR values and can be applied in routine clinical practice.